The Political Economy of the International Tax Transparency Agenda in the G20/OECD Context - Ludger Schuknecht; Vincent Siegerink (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper empirically analyses the motives underlying progress in implementing multilateral tax transparency standards. The results point to the protection of domestic special interests as a potential motive behind slower and less rigorous implementation. In particular, jurisdictions with a significant share of global offshore wealth and to some extent those that host shell company activity, progress less in adopting and implementing the AEOI and EOIR standards. High tax jurisdictions seem to make more progress, while those with significant wealth held offshore seem to lag behind. These special interest considerations, however, may have declined over time as participation became more global and compliance improved. There is also evidence that reputational motives and preceding bilateral collaboration mattered for the speed and comprehensiveness of participation.
Keywords: D70; F53; H26; 330; policy coordination; international public goods; tax transparency and coordination; information exchange